2018
DOI: 10.5435/jaaos-d-16-00551
|View full text |Cite
|
Sign up to set email alerts
|

Functional Outcomes and Complications After Oncologic Reconstruction of the Proximal Humerus

Abstract: All three articular oncologic shoulder reconstructions were comparable in terms of function. This large series confirms a higher fracture rate in OAs, which explains the observed higher revision rate and apparent lower survival rate in this subgroup.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 9 publications
3
27
0
Order By: Relevance
“…Most patients experienced one or more major complications such as caput humeri absorption or fracture; thus, the abductor mechanism was disrupted in almost all of these patients. Although excellent long-term outcomes were rare in our series, a flail shoulder is often the best alternative for the patient who does not need to use the hand in space; the same was reported by other authors [7][8][9][10][11][12][13][14][15][16][17]23]. We also find that functions of the elbow, wrist, and hand remained in a flail limb and can meet the requirements of daily life with the help of an orthotic or the contralateral hand.…”
Section: Discussionsupporting
confidence: 83%
“…Most patients experienced one or more major complications such as caput humeri absorption or fracture; thus, the abductor mechanism was disrupted in almost all of these patients. Although excellent long-term outcomes were rare in our series, a flail shoulder is often the best alternative for the patient who does not need to use the hand in space; the same was reported by other authors [7][8][9][10][11][12][13][14][15][16][17]23]. We also find that functions of the elbow, wrist, and hand remained in a flail limb and can meet the requirements of daily life with the help of an orthotic or the contralateral hand.…”
Section: Discussionsupporting
confidence: 83%
“…However, Wang et al, who found a much lower complication rate (33%), concluded that functional outcomes were better with allograft reconstruction. Nota et al found similar functional outcomes and no statistically significant difference in survival among the groups.…”
Section: Discussionmentioning
confidence: 89%
“…19,[20][21][22][23][24] Five investigations comparing alternative reconstructive methods detected no significant TESS differences. [25][26][27][28][29] Moreover, Jones highlighted that TESS could not distinguish between resections of the anterior compartment that involved or spared the femoral and sciatic nerves. 30 In contrast, Davidge and Griffin identified that more extensive resections had poorer functional outcomes.…”
Section: Toronto Extremity Salvage Scorementioning
confidence: 99%
“…One study concluded that patients undergoing partial rather than total scapulectomy had less QOL impairments while the other evaluated the effectiveness of proximal humerus reconstruction and found no significant differences between osteoarticular allografts, endoprosthesis and allograft prosthetic composites. 27,52 Wilke compared limb salvage and amputation and found that while both had significantly worse function, limb salvage patients experienced lower rates of depression and sleep disturbance compared to the general U.S. population. 53…”
Section: Toronto Extremity Salvage Scorementioning
confidence: 99%